PENINGKATAN HASIL BELAJAR IPA MATERI ENERGI SEKITAR MELALUI MODEL PROJECT BASED LEARNING PADA PESERTA DIDIK KELAS III SDN DUREN SAWIT 13 PAGI JAKARTA TIMUR - Aidhella Tyas Permatasari; Dina Rahmi Darman; Endang M. Kurnianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve science learning outcomes on the topic of energy around us through the implementation of the Project Based Learning (PjBL) model for third-grade students at SDN Duren Sawit 13 Pagi, East Jakarta. Students’ participation during the learning process tended to be less optimal, resulting in low participation, limited understanding of science concepts, and low science learning outcomes. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages conducted in two cycles. The research subjects were 31 third-grade students. Data collection techniques included observation, learning outcome tests, and documentation. The data were analyzed using qualitative and quantitative descriptive methods. The results showed that the implementation of the Project Based Learning model improved teacher activity, student participation, and students’ science learning outcomes. In Cycle I, learning mastery reached 75%, teacher activity was 75%, and student activity was 70%. In Cycle II, teacher and student activities increased to 100%, while learning mastery also improved to 100%. Therefore, the Project Based Learning model proved effective in improving students’ understanding and science learning outcomes on the topic of energy around them.